Territorialidades y organización política indígena en Vaca Muerta. La reconstitución del lof Campo Maripe (Neuquén, Argentina) - Sabrina Aguirre (Nuevo mundo - Mundos Nuevos, 2021)
This paper analyzes the reconstitution of the mapuce community Campo Maripe, studying the path it followed since the settlement of the founding family in Añelo, in the province of Neuquen, to understand the number of conditions in which it survived in its territory, and finally its rearticulation as a mapuche community. The story of the Campo family, settled in “Fortin Vanguardia” in 1927, is deeply linked to the history of the town of Añelo and to the political changes within the province, that have enabled the development of different territorialities in the eastern part of Neuquen, currently characterized by the extraction of hydrocarbons by conventional and non-conventional means, in the Vaca Muerta geological formation. The cleavages in the processes of appropriation and use of land in Añelo and the indigenous possibilities to develop their own territorialities are reviewed, to analyze the territorial marginalization and the dismemberment of the community in the seventies. Finally, the process of communitarian reconstitution in the 21st century, in the context of conflicts, is approached. To do so, written documents and oral testimonies are used, both from the author’s ethnographic fieldwork and from the one carried out by other investigators.